The interaction factor image and the technical professional ([S.l.] : Media Design and Production, 1993)
Focused on interaction factor that covers recognizing professional expectations, communication and sculpting a professional image.
Produced for National Technological University and U K Engineering Continuing Education Office by Media Design & Production
Presenter: Phillip Van Hooser
Keywords: Interaction (Philosophy); Image (Philosophy); Professional employees